T-cell immunity to SARS-CoV-2: what if the known best is not the optimal course for the long run? Adapting to evolving targets - Nowill, Alexandre E.; Caruso, Manuel; de Campos-Lima, Pedro O. (Frontiers in Immunology, 2023)
Humanity did surprisingly well so far, considering how unprepared it was to respond to the coronavirus disease 2019 (COVID-19) threat. By blending old and ingenious new technology in the context of the accumulated knowledge on the virology and immunology of other human coronaviruses, several vaccine candidates were produced and tested in clinical trials in record time. Today, five vaccines account for the bulk of the more than 13 billion doses administered worldwide. This review helps navigating the very large literature on T cell immunity induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and vaccination. We examine the successes and shortcomings of the vaccinal protection in the light of the emergence of variants of concern with breakthrough potential. Finally, we discuss the role that innate-induced trained immunity and adaptive-induced immune response resetting may have in antiviral heterologous protection.